Comparison of Accessibility to Cavernous Sinus Areas Throughout Endonasal, Transorbital, and Transcranial Approaches: Anatomic Study With Quantitative Analysis. Issue 4 (16th April 2023) - Santos, Carlos; Guizzardi, Giulia; Di Somma, Alberto; Lopez, Patricia; Mato, David; Enseñat, Joaquim; Prats-Galino, Alberto
Abstract : BACKGROUND: The cavernous sinus (CS) is accessed through several approaches, both transcranially and endoscopically. The transorbital endoscopic approach is the newest proposed route in the literature. OBJECTIVE: To quantify and observe the areas of the CS reach from 2 endoscopic and 1 transcranial approaches to the CS in the cadaver laboratory. METHODS: Six CSs were dissected through endoscopic endonasal, transorbital endoscopic, and transcranial pterional approaches, with previous implanted references for neuronavigation during the dissection. Point registration was used to mark the CS exposure and limits through each approach for later area and volume quantification through a computerized technique. RESULTS: The endoscopic endonasal approach reaches most of the CS except part of the sinus's superior, lateral, and posterior regions. The area exposed through this approach was 210 mm 2, and the volume was 1165 mm 3 . The transcranial pterional approach reached the superior and part of the lateral sides of the sinus, not allowing good access to the medial side. The area exposed through this approach was 306 m 2, whereas the volume was 815 m 3 . Finally, the transorbital endoscopic approach accessed the whole lateral side of the sinus but not the medial one. The area exposed was the greatest, 374 m 2, but its volume was the smallest, 754 m 3 . CONCLUSION: According to our results, the endonasal endoscopic approach is the direct route to access the medial, inferior, and part of the superior CS compartments. The transorbital approach is for the lateral side of the CS. Finally, the transcranial pterional approach is the one for the superior side of the CS.